The Twenty-First Century Social Media Research: A Bibliometric Review - Anthony Mensah; Peter Agbedemnab; Nasir Asiedu (International Journal of Information Science and Management)
This study investigated the intellectual framework of literature on social media and highlighted the new trends in social media research. The search for relevant publications on the topic on May 28, 2023, began with the use of the Scopus database, which resulted in the retrieval of 157,474 documents covering the years 1941 to 2024. Following filtering, the total number of records, which covered the years 2000 through to 2022, was reduced to 50,872, and the same was used for the data analysis using VOSviewer. The analysis involved co-word analysis and citation analysis, which made it possible to uncover the patterns of research topics and aided the identification of influential publications and authors. The findings of the study therefore revealed that research on social media has received significant attention from scholars globally, with 2022 recording the highest number of publications. Results from the country analysis indicated that the geographical closeness of countries does not create collaborative advantages for authors. The institutional analysis also revealed that the ESCP Business School and North-West University are the top two leading institutions by reference to the number of citations. Regarding the most cited publication, the paper, “Users of the World, Unite! The Challenges and Opportunities of social media,” authored by Kaplan, A. M., & Haenlein, M., in 2010, received the most citations within the period under review. The study therefore recommends that future studies should use the two academic database,s which are Scopus and Web of Science to conduct an in-depth survey on social media research in the 21st century.